2021
DOI: 10.1186/s12944-021-01571-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive skin cholesterol testing: a potential proxy for LDL-C and apoB serum measurements

Abstract: Background Lipid management is the first line of treatment for decreasing the incidence of cardiovascular events in patients with coronary heart disease (CHD), and a variety of indicators are used to evaluate lipid management. This work analyses the differences in LDL-C and apoB for lipid management evaluation, as well as explores the feasibility of skin cholesterol as a marker that can be measured non-invasively for lipid management. Methods The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Atherosclerosis may result in myocardial ischemia via two different identities, acute coronary syndrome (ACS, type 1 MI) and prolonged myocardial oxygen supply–demand imbalance (type 2 MI) ( Smit et al, 2020 ). ACS occurs because of an unstable plaque rupture or endothelial ulceration and is influenced by factors such as inflammation ( Casscells et al, 2003 ) and hyperlipidemia ( Lai et al, 2021 ). Our study showed that among the top ten KEGG pathways associated with XML injection treatment, five were associated with inflammation and hyperlipidemia, including “PPAR signaling pathway,” “arachidonic acid metabolism,” “regulation of lipolysis in adipocytes,” and “fat digestion and absorption” ( Figure 3D ).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis may result in myocardial ischemia via two different identities, acute coronary syndrome (ACS, type 1 MI) and prolonged myocardial oxygen supply–demand imbalance (type 2 MI) ( Smit et al, 2020 ). ACS occurs because of an unstable plaque rupture or endothelial ulceration and is influenced by factors such as inflammation ( Casscells et al, 2003 ) and hyperlipidemia ( Lai et al, 2021 ). Our study showed that among the top ten KEGG pathways associated with XML injection treatment, five were associated with inflammation and hyperlipidemia, including “PPAR signaling pathway,” “arachidonic acid metabolism,” “regulation of lipolysis in adipocytes,” and “fat digestion and absorption” ( Figure 3D ).…”
Section: Discussionmentioning
confidence: 99%